2016
DOI: 10.1186/s12968-016-0226-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance imaging of myocardial oedema following acute myocardial infarction: Is whole heart coverage necessary?

Abstract: BackgroundAAR measurement is useful when assessing the efficacy of reperfusion therapy and novel cardioprotective agents after myocardial infarction. Multi-slice (Typically 10-12) T2-STIR has been used widely for its measurement, typically with a short axis stack (SAX) covering the entire left ventricle, which can result in long acquisition times and multiple breath holds. This study sought to compare 3-slice T2-short-tau inversion recovery (T2- STIR) technique against conventional multi-slice T2-STIR techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…It has been suggested that to avoid this bias, one could use a multislice technique. 40 Third, the CMR 1 was later on the control group so edema could not be present just because it was done later than the liraglutide group. The number of patients could be increased to try to minimize this effect.…”
Section: Study Limitationsmentioning
confidence: 99%
“…It has been suggested that to avoid this bias, one could use a multislice technique. 40 Third, the CMR 1 was later on the control group so edema could not be present just because it was done later than the liraglutide group. The number of patients could be increased to try to minimize this effect.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Furthermore, when MSI was calculated using whole LV coverage for MI size and the 3 slices for AAR as previously done by Hamshere et al . 12 , this approach underestimated the AAR in 7/48 patients for T2 mapping and 3/30 patients for T1 mapping and resulted in a negative MSI, which is not plausible in practice and would impact on mean MSI in a cardioprotection study. In the clinical setting, it is difficult to know whether a patient would have MSI more than or less than 0.50 prior to acquiring the images and the analysis the MI size and AAR data and therefore full LV acquisition of T1 or T2 maps is recommended when the edema-based AAR needs to be assessed.…”
Section: Discussionmentioning
confidence: 95%
“…The accurate quantification of the AAR conventionally requires full left ventricular (LV) coverage. Recently, a 3-slice approach has been proposed for T2-weighted STIR imaging, with the obvious benefit of shorter scan and analysis time 12 . The main aim of this study was to assess whether the 3-slice approach will also perform as well as full LV coverage, using T1 and T2 mapping to delineate the AAR.…”
Section: Introductionmentioning
confidence: 99%
“…The area-at-risk is useful when assessing the efficacy of reperfusion therapy and novel cardioprotective agents after myocardial infarction. In this study by Hamshere and co-workers [ 79 ], CMR was performed in 167 patients after successful primary percutaneous coronary intervention with 82 patients undergoing a novel 3-short axis T2-STIR protocol and 85 both the novel 3-short axis protocol and a conventional 10 slice short-axis late gadolinium enhancement (LGE) protocol. The 3-slice T2-STIR and 10 slice LGE area-at-risk imaging showed a strong correlation with each other and with the angiographic risk scores.…”
Section: Cardiomyopathiesmentioning
confidence: 99%